A Buried Middle Archaic Site in the Tucson Basin. Issue 1 (2nd January 2021) - Huckell, Bruce B.; Birkmann, Joseph M.; Haynes, C. Vance
Abstract : Despite great gains in knowledge about the Late Archaic/Early Agricultural period in the Tucson Basin, understanding of the Middle Archaic period remains slim. This paper reports on volunteer investigations at three buried Archaic sites within the Santa Cruz River floodplain: the Joe Ben Site (AZ BB:13:11), AZ BB:13:70, and an unnumbered locus north of the latter. The AZ BB:13:70 artifact assemblage and the Joe Ben site records suggest small-scale, short-term, repeated use of this portion of the Santa Cruz floodplain and the Santa Rita bajada by foragers between 4200 and 5100 BP, continuing into the Late Archaic/Early Agricultural period. Though assumed to be absent within the southern Southwest during the Middle and Late Holocene, the skull of a juvenile bison at AZ BB:13:70 and post-cranial bison bones at the unnumbered locus indicate their sporadic presence within the Tucson Basin during this period and their occasional exploitation by Middle Archaic hunters.